ANTI-MODIFIED PROTEIN ANTIBODY RESPONSE PATTERN INFLUENCES THE RISK FOR DISEASE RELAPSE IN RHEUMATOID ARTHRITIS PATIENTS TAPERING DISEASE MODIFYING ANTI-RHEUMATIC DRUGS - Figueiredo, C.; Bang, H.; Cobra, J. F.; Englbrecht, Matthias; Hueber, A. J.; Haschka, J.; Manger, Bernhard; Kleyer, A.; Reiser, M.; Finzel, S.; Tony, H-P.; Kleinert, S.; et al. (2016)
EVALuna2:13494

Cost-effective tapering algorithm in patients with rheumatoid arthritis: Combination of multibiomarker disease activity score and autoantibody status - Hagen, Melanie; Englbrecht, Matthias; Haschka, Judith; Reiser, Michaela; Kleyer, Arnd; Hueber, Axel; Manger, Bernhard; Figueiredo, Camille; Cobra, Jayme Fogagnolo; Tony, Hans-Peter; Finzel, Stephanie; Kleinert, Stefan; et al. (Journal of Rheumatology, 2019)
Objective. To analyze the effect of a risk-stratified disease-modifying antirheumatic drug (DMARD)- tapering algorithm based on multibiomarker disease activity (MBDA) score and anticitrullinated protein antibodies (ACPA) on direct treatment costs for patients with rheumatoid arthritis (RA) in sustained remission. Methods. The study was a posthoc retrospective analysis of direct treatment costs for 146 patients with RA in sustained remission tapering and stopping DMARD treatment, in the prospective randomized RETRO study. MBDA scores and ACPA status were determined in baseline samples of patients continuing DMARD (arm 1), tapering their dose by 50% (arm 2), or stopping after tapering (arm 3). Patients were followed over 1 year, and direct treatment costs were evaluated every 3 months. MBDA and ACPA status were used as predictors creating a risk-stratified tapering algorithm based on relapse rates. Results. RA patients with a low MBDA score (< 30 units) and negative ACPA showed the lowest relapse risk (19%), while double-positive patients showed high relapse risk (61%). In ACPA-negative and MBDA-negative (< 30 units), and ACPA or MBDA single-positive (> 30 units) groups, DMARD tapering appears feasible. Considering only patients without flare, direct costs for synthetic and biologic DMARD in the ACPA/MBDA-negative and single positive groups (n = 41) would have been ϵ372,245.16 for full-dose treatment over 1 year. Tapering and stopping DMARD in this low-risk relapse group allowed a reduction of ϵ219,712.03 of DMARD costs. Average reduction of DMARD costs per patient was ϵ5358.83. Conclusion. Combining MBDA score and ACPA status at baseline may allow risk stratification for successful DMARD tapering and cost-effective use of biologic DMARD in patients in deep remission as defined by the 28-joint count Disease Activity Score using erythrocyte sedimentation rate.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Anticyclic Citrullinated Protein Antibodies; Drug Costs; Multibiomarker Disease Activity; Remission; Rheumatoid Arthritis; Tapering

ELEVATED MULTI-BIOMARKER DISEASE ACTIVITY (MBDA) PREDICTS RELAPSES IN RA PATIENTS IN SUSTAINED REMISSION TAPERING TUMOUR NECROSIS FACTOR INHIBITOR THERAPY-RESULTS FROM THE RANDOMIZED CONTROLLED RETRO STUDY - Rech, Jürgen; Hagen, M.; Englbrecht, M.; Haschka, J.; Reiser, M.; Kleyer, A.; Hueber, A.; Manger, Bernhard; Figuereido, C.; Cobra, J. Fogagnolo; Tony, H-P.; Finzel, S.; et al. (2017)
EVALuna2:34452

FACTORS ASSOCIATED WITH PERSISTENT DRUG-FREE REMISSION IN PATIENTS WITH RHEUMATOID ARTHRITIS - Valor, Larissa; Hagen, Melanie; Reiser, Michaela; Kleyer, Arnd; Hartmann, Fabian; Manger, Bernhard; Schett, Georg; Rech, Jürgen; Tascilar, Koray; Haschka, J.; Englbrecht, Matthias; Hueber, Axel; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-16

Hard palate hyperpigmentation - a rare side effect of antimalarials - Manger, Karin; von Streitberg, Ulrich; Seitz, Gerhard; Kleyer, Arnd; Manger, Bernhard (Arthritis and Rheumatology, 2017)
A 50-year old female Caucasian patient with marked xerostomia, xerophthalmia, relapsing parotid swelling, arthralgias, and fatigue had been treated with chloroquine diphosphate (250 mg/day) for four years, when a painless bluish-grey hyperpigmentation of her hard palate was noticed during one of her rheumatologic follow-up visits (A). To rule out malignancy or infection, a mucosal biopsy was performed and histology showed subepithelial granular pigment depositions among collagen fibres and within macrophages (B). Perl's Prussian blue staining confirmed that these deposits contained hemosiderin (C). This article is protected by copyright. All rights reserved.
EVALuna2:13448

Impact of Cytokine Inhibitor Therapy on the Prevalence, Seroconversion Rate, and Longevity of the Humoral Immune Response Against SARS-CoV-2 in an Unvaccinated Cohort - Simon, David; Tascilar, Koray; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, Johanna; Liphardt, Anna-Maria; Schönau, Verena; et al. (Arthritis and Rheumatology, 2022)
Objective To investigate the impact of biologic disease-modifying antirheumatic drug (bDMARD) treatment on the prevalence, seroconversion rate, and longevity of the humoral immune response against SARS-CoV-2 in patients with immune-mediated inflammatory diseases (IMIDs). Methods Anti-SARS-CoV-2 IgG antibodies were measured in a prospective cohort of health care professional controls and non-health care controls and IMID patients receiving no treatment or receiving treatment with conventional or biologic DMARDs during the first and second COVID-19 waves. Regression models adjusting for age, sex, sampling time, and exposure risk behavior were used to calculate relative risks (RRs) of seropositivity. Seroconversion rates were assessed in participants with polymerase chain reaction (PCR)-positive SARS-CoV-2 infection. Antibody response longevity was evaluated by reassessing participants who tested positive during the first wave. Results In this study, 4,508 participants (2,869 IMID patients and 1,639 controls) were analyzed. The unadjusted RR (0.44 [95% confidence interval (95% CI) 0.31-0.62]) and adjusted RR (0.50 [95% CI 0.34-0.73]) for SARS-CoV-2 IgG antibodies were significantly lower in IMID patients treated with bDMARDs compared to non-health care controls (P < 0.001), primarily driven by treatment with tumor necrosis factor inhibitors, interleukin-17 (IL-17) inhibitors, and IL-23 inhibitors. Adjusted RRs for untreated IMID patients (1.12 [95% CI 0.75-1.67]) and IMID patients receiving conventional synthetic DMARDs (0.70 [95% CI 0.45-1.08]) were not significantly different from non-health care controls. Lack of seroconversion in PCR-positive participants was more common among bDMARD-treated patients (38.7%) than in non-health care controls (16%). Overall, 44% of positive participants lost SARS-CoV-2 antibodies by follow-up, with higher rates in IMID patients treated with bDMARDs (RR 2.86 [95% CI 1.43-5.74]). Conclusion IMID patients treated with bDMARDs have a lower prevalence of SARS-CoV-2 antibodies, seroconvert less frequently after SARS-CoV-2 infection, and may exhibit a reduced longevity of their humoral immune response.
CRIS-Team WoS Importer:2022-04-08

LONG-TERM HUMORAL RESPONSE TO SARS-COV-2 VACCINATION IN PATIENTS WITH IMMUNE-MEDIATED INFLAMMATORY DISEASE - Tascilar, Koray; Simon, David; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, J.; Liphardt, Anna-Maria; Schönau, Verena; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

MULTI-BIOMARKER DISEASE ACTIVITY AND AUTOANTIBODY STATUS LEAD TO COST EFFECTIVE TAPERING ALGORITHMS IN RHEUMATOID ARTHRITIS PATIENTS IN SUSTAINED REMISSION - Hagen, Melanie; Englbrecht, Matthias; Haschka, J.; Reiser, M.; Kleyer, Arnd; Hueber, A.; Manger, Bernhard; Figuereido, C.; Cobra, J. Fogagnolo; Tony, H. -P.; Finzel, S.; Kleinert, S.; et al. (2017)
EVALuna2:34451

Patients Receiving Cytokine Inhibitors Have Low Prevalence of SARS-CoV-2 Infection - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Patients with immune-mediated inflammatory diseases receiving cytokine inhibitors have low prevalence of SARS-CoV-2 seroconversion - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (Nature Communications, 2020)
Immune-mediated inflammatory diseases (IMIDs) of the joints, gut and skin are treated with inhibitors of inflammatory cytokines. These cytokines are involved in the pathogenesis of coronavirus disease 2019 (COVID-19). Investigating anti-SARS-CoV-2 antibody responses in IMIDs we observe a reduced incidence of SARS-CoV-2 seroconversion in IMID patients treated with cytokine inhibitors compared to patients receiving no such inhibitors and two healthy control populations, despite similar social exposure. Hence, cytokine inhibitors seem to at least partially protect from SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2020-08-07

Prediction of Disease Relapses By Multi-Biomarker Disease Test Activity in Rheumatoid Arthritis Patients Tapering DMARD Treatment - Rech, Jürgen; Hueber, Axel; Englbrecht, Matthias; Finzel, Stephanie; Haschka, Judith; Manger, Bernhard; Kleyer, Arnd; Reiser, Michaela; Tony, Hans-Peter; Kleinert, Stefan; Feuchtenberger, Martin; Fleck, Martin; et al. (2015)
EVALuna2:13331

Pseudoacrocyanosis: a case for telemedicine in rheumatology - Manger, Bernhard; Manger, Karin (RMD Open, 2022)
Here we describe three patients, two of them medical doctors, who were concerned about striking, sudden-onset bluish discoloration of their hands. After sending electronic images of these changes to befriended rheumatologists, one simple anamnestic question could unveil the surprising cause of their symptoms.
CRIS-Team WoS Importer:2022-09-23

RETRO - STUDY OF REDUCTION OF THERAPY IN PATIENTS WITH RHEUMATOID ARTHRITIS IN ONGOING REMISSION - Haschka, J.; Englbrecht, Matthias; Hueber, Axel; Manger, Bernhard; Kleyer, Arnd; Reiser, M.; Finzel, Stephanie; Tony, H. -P.; Kleinert, S.; Feuchtenberger, M.; Fleck, M.; Manger, Karin; et al. (2015)
EVALuna2:34460

Risk of infections in rheumatoid arthritis patients treated with tocilizumab - Lang, Veronika R.; Englbrecht, Matthias; Rech, Jürgen; Nüsslein, Hubert; Manger, Karin; Schuch, Florian; Tony, Hans-Peter; Fleck, Martin; Manger, Bernhard; Schett, Georg; Zwerina, Jochen (Rheumatology, 2012)
Objectives: To investigate the occurrence and risk factors for infections in RA patients treated with tocilizumab. Methods: A cohort of all RA patients (n = 112) starting tocilizumab therapy between October 2008 and March 2010 in Northern Bavaria was screened for infections. Mild/moderate and severe infections were recorded. Multivariate logistic regression analysis was used to define risk factors for infection. Results: Overall, 26 patients developed infections [23.2%; 58.0/100 patient-years (py)], 18 of them were mild to moderate (16.1%, 40.1/100 py) and 8 were severe (17.9/100 py). Concomitant use of LEF and prednisone, high disease activity and previous therapy with rituximab were associated with the occurrence of mild/moderate infections. Severe infections were related to longer disease duration, exposure to more than three previous DMARDs and concomitant therapy with proton-pump inhibitors. Conclusion: The rate of infection in RA patients treated with tocilizumab in clinical practice is higher than in the clinical trial populations. Increased attention should especially be given to patients with longer disease duration, previous exposure to multiple DMARDs, i.e. previous exposure to rituximab and those receiving concomitant LEF, prednisone or proton-pump inhibitor treatment. © The Author 2011. Published by Oxford University Press on behalf of the British Society for Rheumatology. All rights reserved.
CRIS-Team Scopus Importer:2021-02-03
Keywords: Infections; Rheumatoid arthritis; Tocilizumab

Successful treatment of adult-onset Still's disease refractory to TNF and IL-1 blockade by IL-6 receptor blockade - Rech, Jürgen; Ronneberger, Monika; Englbrecht, Matthias; Finzel, Stephanie; Katzenbeisser, Julia; Manger, Karin; Manger, Bernhard; Schett, Georg (Annals of the Rheumatic Diseases, 2011)
CRIS-Team Scopus Importer:2021-02-03